Analysis of metadata in art museum institutions of the "Ibermuseos" Cooperation Program - Tarré Alonso, Beatriz; Díaz-Redondo, Carlos; Monteiro de Barros, Camila; Cardozo Padilha, Renata (Revista General de Información y Documentación, 2025)
The metadata used in the cataloging records of art museums participating in the “Ibermuseos” Cooperation Program is analyzed, evaluating its depth, standardization, and public accessibility through digital platforms. With a mixed quantitative and qualitative approach, the research emphasizes a contextualized understanding of museological practices and the complex interrelations between theory and data. A structured questionnaire was designed and applied to a sample of 730 museums selected from the Ibero-American Museum Registry. After conducting a pretest and making various methodological adjustments, 77 responses were obtained, representing approximately 10% of the initial sample. The results reveal variability in metadata usage and underscore the importance to improve database updates and terminological standardization within Ibermuseos. This study provides key elements to strengthen interregional cooperation and democratize access to knowledge in the museological field.